PRESCRIPTION PATTERNS, ADHERENCE, AND SIDE EFFECTS OF MEDICATION USE IN DEPRESSION AND ANXIETY PATIENTS IN THE OUTPATIENTS AT WEST JAVA PROVINCIAL MENTAL HOSPITAL - Laila Najmi, Reza
Based on data from the Basic Health research (Riskesdas, 2018), there were 700,000 Indonesians (15 years and over) who have emotional mental disorders and depression. This study aims to assess the prescribing patterns, medication adherence, and side effects of patients with depression and anxiety at the Outpatient at the West Java Provincial Mental Hospital. This study used an observational method with a descriptive cohort design. At baseline, patients filled out a questionnaire regarding socio-demographic data, while diagnoses and prescriptions were confirmed from medication record data. One month after baseline, data on medication adherence and medication adverse reaction were collected using a different questionnaire. Socio-demographic analysis showed that the majority of patients were female (63.2%), aged 19-29 years (43.4%), high school education (53.9%), jobless (65.8), no monthly income (48.7%), and married (53.9%). Analysis of PDD/DDD ratio results showed that the patient had been treated using SSRIs, atypical antipsychotics, and benzodiazepines. The side effects most often experienced by patients were feeling nervous or anxiety (13.16%). The statistical analysis showed that drug adjustment (an increase/decrease in dose or change in medication) was more likely to be found in patients with lower levels of education (OR 2,577, 95%Cl 1,056-6,292) and non-adherence patiens aret more likely to be found in patients with comorbidities (OR 0,252, 95%Cl 0,078-0,917). There was no association between all socio-demographic variables and drug adverse reaction. The study found that the prescribing patterns for patients with depression and anxiety were in line with the literature, patients had high medication adherence, and reported minimal incidence of side effects at West Java Provincial Mental Hospital